Editorial Boarding - Zandwais, ANA; Tutikian, Jane; Campos, Maria (Revista Conexão Letras, 2016)
We present with great honour to our colleagues and to the scientifi c academy the number 16 of Journal Conexão Letras – Post Graduate Studies in Linguistics and Literature at Federal University of Rio Grande doSulState – entitled “Philosophycal and Linguistc Contributions of Bakhtin Circle to Linguistic and Literary Studies.” This volume became special for us by the following reasons: a) it is our fi rst bilingual number (Portuguese –English) produced by a group of Brazilian Professors from the Universities of São Paulo, Pernambuco, Brasília, Rio Grande do Sul, Taubaté and with a special collaboration of Professor Craig Brandist, coordinator of Bakhtin Centre at University of Sheffi eld –UK.; b) the subjects that organize this number have been object of several discussions during one semester, a period when all collaborators thought about how they could present their studies under theoretical and analytical bases developed by Bakhtin Circle.